2016
DOI: 10.1159/000452269
|View full text |Cite
|
Sign up to set email alerts
|

Protease-Activated Receptor 1 Contributes to Angiotensin II-Induced Cardiovascular Remodeling and Inflammation

Abstract: Background: Angiotensin II (Ang II) plays an important role in cardiovascular disease. It also leads to the activation of coagulation. The coagulation protease thrombin induces cellular responses by activating protease-activated receptor 1 (PAR-1). We investigated whether PAR-1 contributes to Ang II-induced cardiovascular remodeling and inflammation. Methods and Results: PAR-1+/+ (wild-type; WT) and PAR-1-/- mice were infused with Ang II (600 ng/kg/min) for up to 4 weeks. In WT mice, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 68 publications
1
23
0
1
Order By: Relevance
“…Notably, this receptor cannot be activated by C3a [ 39 ]. Activation of PAR1 and 4 by C4a leads to cellular activation and enhanced endothelial permeability [ 39 ], and PAR1 has been previously implicated in, e.g., cardiac remodeling [ 40 ] and hepatic injury [ 43 ]. Notably, C4a cannot signal via the C3aR [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this receptor cannot be activated by C3a [ 39 ]. Activation of PAR1 and 4 by C4a leads to cellular activation and enhanced endothelial permeability [ 39 ], and PAR1 has been previously implicated in, e.g., cardiac remodeling [ 40 ] and hepatic injury [ 43 ]. Notably, C4a cannot signal via the C3aR [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…5B and C). Previous studies have reported crosstalk between coagulation and inflammation (Antoniak et al2016(Antoniak et al , 2013(Antoniak et al , 2016aAndrade et al 2013;Wilson et al 2014;Azeredo et al 2015;Yang and Tang 2016). Therefore, we determined if anticoagulation affected the recruitment of…”
Section: Anticoagulation Does Not Affect Viral Genomes or Inflammationmentioning
confidence: 93%
“…Total lung RNA was extracted using TRIzol (Life Technologies, Carlsbad, CA). RNA was reverse transcribed into cDNA using the iScript ™ RT Supermix (Bio-Rad) and the levels of H1N1 PR/8 genomes were quantified by realtime PCR using SSoFast ™ Probes Supermix and a Bio-Rad cycler (Bio-Rad) as described (Antoniak et al 2016(Antoniak et al , 2013(Antoniak et al , 2016a. Rpl4 was used for normalization.…”
Section: Rna Isolation and Rt-pcrmentioning
confidence: 99%
“…First, it up-regulates tissue factor and levels of plasminogen activator inhibitor 1. Second, it reduces antithrombotic proteins as antithrombin III [ 103 , 104 ].…”
Section: Dendritic Cell and Hypercoagulabilitymentioning
confidence: 99%